WRITING INTRODUCTION SECTIONS OF RESEARCH ARTICLES IN APPLIED LINGUISTICS: CROSS-LINGUISTIC STUDY OF NATIVE AND NON-NATIVE WRITERS - Farnia, Maryam; Barati, Safoora (Universitas Pendidikan Indonesia, 2017)
Genre studies allow researchers to observe the repeated communicative functions and their linguistic components in different genres (Brett, 1994). Writing the introduction section is a tough and burdensome task for both native and non-native speakers (Swales Feak, 1994). Hence, the present study aimed to investigate the generic organization of English research article introductions written by native English and Iranian non-native speakers of English. A total of 160 published articles were selected from established journals in Applied Linguistics. Following Swales’ (2004) Create A Research Space (CARS) model, the researchers analyzed the articles for their specific generic patterns. Findings displayed that native English writers used significantly more strategies than Iranian non-native speakers of English, yielding richer texts. The findings of the present study contribute to the current knowledge of cross-cultural studies in academic writing to non-native English speakers in general and to non-native English novice writers in particular. Built on Swales’ (2004) CARS model, the study describes how introduction sections are developed in English by native and non-native speakers, offering insights into ESP/EAP writing pedagogy.